A Hypothesis-Driven, Near-Peer Physical Diagnosis Module on Streptococcal Pharyngitis Within the Pediatrics Clerkship - Lindsay Podraza; Lauren S. Starnes; Kyle Langford; Logan Garfield; Allyson Metro; Alyssa Schlotman; Nicole Chambers; Maya Neeley (Association of American Medical Colleges, 2024)
Introduction In busy clinical settings, there is limited time to teach physical examination (PE) and procedural skills, particularly when the traditional head-to-toe PE approach is time-consuming. Near-peer teaching of a more efficient approach, the hypothesis-driven PE (HDPE), increases students' learning opportunities. We developed a near-peer HDPE module to improve medical student confidence, knowledge, and skills for diagnosing and managing streptococcal pharyngitis. Methods During this 1-hour module, residents taught the diagnostic approach for a patient with sore throat and facilitated small groups for practicing PE and throat swab skills. We assessed students using pre- and postmodule surveys including Likert-scale confidence scores (1 = not at all confident, 5= extremely confident), multiple-choice knowledge questions, and a skills rubric. A control group was surveyed at clerkship conclusion. Results Of the 71 pediatric clerkship students who participated, 69 (97%) completed premodule surveys and 65 (91%) completed skills assessments. Twenty-eight (39%) completed postmodule surveys and skill assessments. After participation, students' survey responses and rubrics indicated significant increase in confidence (Mdnpre = 2 [IQR = 1,2], Mdnpost = 4 [IQR = 4,5]; p < .001), knowledge (Mpre = 40%, Mpost = 77%; p < .001), and skills (Mpre = 5.3, Mpost = 7.5; p < .01). Participating students also had significantly higher confidence (p < .005) and knowledge (p < 0.01) compared to the control group. Discussion This near-peer HDPE module improved students' knowledge, confidence, and skills related to streptococcal pharyngitis diagnosis and management and achieved compliance for a required clerkship skill.